MEANING AND FUNCTION OF WORD FORMATION IN THE NFL.COM NEW - Kristina Dewi; Rr. Arielia Yustisiana (Universitas Katolik Widya Mandala Surabaya, 2023)
Because of the interest and fans of American football in Indonesia, there is a need for information and understanding about the word formation in American football. Understanding the word formation process is very important in everyday life to communicate and understand each other. The research aimed to analyze the word formation, type, meaning, and function of various languages of American football on the official NFL.com news website. The research is classified as a qualitative descriptive one. The research data are in the form of words, phrases, and clauses containing word formation found in NFL.com news published in November – December 2022. The findings were that there were four-word formations which were found: compounding, borrowing, acronym, and derivation. The results showed that the highest data frequency related to word formation is compounding. Moreover, there were 6 types, that is, injury, players, rules of time, game techniques, scores, and teams. The type of team appeared most often. Each datum has a different meaning, and function depending on the context of the sentence.